Study of Some physical and chemical properties of sand dune of lower Mesopotamian Plain - Hussain, G. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This investigation was conducted to examine some physical and chemical properties of sand dunes collected from Basrah (1 ’2 and 3) ’Nassiriya (4 and 5) and Amara (6) provinces that situated in lower Mesopotamia plain. The results indicate clearly that the dominant particles in the samples were sand that were ranging from (81) % to (97) %, however the aggregated size of (0.1 - 0.25) mm were predominates in the investigated sand dunes of the region . Also the study shows that the content of the organic matter and potassium ions were very low (0.1- 0.4% ’0.02 -0.22 meq I 100 gm soil. Further more the current result shows high a percentage of calcium carbonate (20.3 - 42.5%). In addition, the study has found an accumulated salt content in sand dunes samples (10.5 - 64.0 mmohs I cm) with a high value of pH (6.5 - 7.4). The sand color ranges from the Orange’s Yellow (10 YR 7/3) to dark olive (7.5 Y 4/3).